Praktik Illegal Fishing Pada Masyarakat Batudaka Kabupaten Tojo Una Una Sulawesi Tengah - Andi Arielsya Juniarto; Andi Octamaya Tenri Awaru (Rayhan Intermedia, 2023)
This research aims to find out: (1) Factors that encourage people to carry out illegal fishing in Batudaka sub-district. (2) Illegal forms of fishing in the Batudaka community. The data collection technique used is interviews/interviews/documentation. Type of descriptive qualitative research. Formally, to find out about illegal fishing practices in Batudaka District. The qualitative data analysis technique goes through three stages, namely data reduction, data presentation, and drawing conclusions. The data validity technique uses validity and reliability testing techniques. The research results show that (1) factors that encourage people to engage in illegal fishing include: economy, livelihood, needs, activities. (2) Illegal forms of fishing in the Batudaka community include: fish bombing, anesthesia, tiger trawling, compressors, and poisoning.